The NBOMe hallucinogenic drug series: Patterns of use, characteristics of users and self-reported effects in a large international sample - Lawn, W.; Barratt, Monica; Williams, M.; Horne, A.; Winstock, A. (Sage Publications, 2014)
The NBOMe compounds are a novel series of hallucinogenic drugs that are potent agonists of the 5-HT2A receptor, have a short history of human consumption and are available to buy online, in most countries. In this study, we sought to investigate the patterns of use, characteristics of users and self-reported effects. A cross-sectional anonymous online survey exploring the patterns of drug use was conducted in 2012 (n = 22,289), including questions about the use of 25B-NBOMe, 25C-NBOMe, and 25I-NBOMe and comparison drugs. We found that 2.6% of respondents (n = 582) reported having ever tried one of the three NBOMe drugs and that at 2.0%, 25I-NBOMe was the most popular (n = 442). Almost all (93.5%) respondents whose last new drug tried was a NBOMe drug, tried it in 2012, and 81.2% of this group administered the drug orally or sublingually/buccally. Subjective effects were similar to comparison serotonergic hallucinogens, though higher ‘negative effects while high’ and greater ‘value for money’ were reported. The most common (41.7%) drug source was via a website. The NBOMe drugs have emerged recently, are frequently bought using the internet and have similar effects to other hallucinogenic drugs; however, they may pose larger risks, due to the limited knowledge about them, their relatively low price and availability via the internet.